PEMBERDAYAAN KELOMPOK TANI (KWT) MELALUI PEMANFAATAN LAHAN PEKARANGAN UNTUK BUDIDAYA TANAMAN SAYURAN DI DESA SUNGAI PUTIH - Zakiyatul Miskiyah; Awatif (AbdiMasya | Hira Institute, 2023)
This research was motivated by problems in the activities of utilizing house yards carried out by the Women Farmers Group (KWT) in Sungai Putih Village, namely the lack of maintenance of the Bumdes yard and village hall, low interest and participation of KWT Sungai Putih, as well as problems with the plants in their respective yards. each member of KWT Sungai Putih. The aim of this research is the process of empowering women farmer groups (KWT) in Sungai Putih Village. This research uses data collection techniques in the form of observation, interviews and documentation. The main target in empowering women farmer groups is women farmers in Sungai Putih Village. In this research, groups of women farmers were able to plant vegetable crops by utilizing yard land in Sungai Putih Village. Apart from that, through empowering this group of women farmers, which is a forum for communication between fellow women farmers and can improve the family economy. In implementing KWT activities, Sungai Putih faced internal and external obstacles. Internal obstacles include low participation in implementing activities, low enthusiasm for planting in their respective yards, lack of motivation, and lack of benefit from this activity. Meanwhile, external obstacles include problems in the nursery, lack of communication between PPL and KWT.